The Impact of Exchange Rate Fluctuations on Financial Markets: A Case Study - Abdessalam Belbali; Samir Ouldbahammou; Abderrahim Belbali; Mohammed Amine Gasmi; Ali Yousfat; Asma Bellaama (Financial Markets, Institutions and Risks)
This study examines the impact of exchange rate fluctuations on the financial market. It provides an empirical analysis of how changes in the Saudi Riyal exchange rate against the US dollar affect the trading index in the Saudi financial market from 2022 to 2024. The study used a set of standard tests, including the Phillips-Perron test to assess the stationarity of time series, and the cointegration test employing the autoregressive distributed lag (ARDL) methodology, alongside the Granger causality test. The results indicated the existence of a long-term equilibrium relationship between the exchange rate and the trading index. In the short run, there is a negative (inverse) relationship between the exchange rate and the trading index, such that a one-unit increase in the exchange rate leads to a decrease of 316.677 points in the Saudi financial market index. The short-term model results reveal that the coefficient of the error correction term indicates the speed at which the trading index in the Saudi financial market returns to its long-term equilibrium value. In each period, the error from the previous period (t-1) is corrected by about 28%, which is considered a weak adjustment factor. However, no causal relationship between the exchange rate and the trading index in the Saudi financial market was identified.